Hans Schäufelin als Maler - Metzger, Christof 1968- (Dt. Verl. für Kunstwiss., 2002)
Presents a lengthy study of the life and work of the German painter Hans Schäufelin (ca. 1480-ca. 1539) along with a catalogue raisonné of his paintings, most of which deal with Christian art and symbolism. The catalogue lists 75 genuine works along with 23 works of artists from the circle of Schäufelin, 133 works erroneously ascribed to the artist, and other works either forged or lost. The catalogue is profusely illustrated with black and white reproductions and 16 color plates of Schäufelin's paintings.
Zugl.: Augsburg, Univ., Diss., 1999. - Rez.: Kunstchronik 57 (2004),4, S. 185-190 (Hartmut Scholz)
Keywords: Schäufelein, Hans <1480?-1539?> - Catalogues raisonnés; Schäufelein, Hans <1480?-1539?> - Oeuvres - Peinture; Schäufelein, Hans <ca. 1480-ca. 1539> -- Catalogs; Schäufelein, Hans Leonhard -- 1480-1540; Schilderijen; Malerei; Hochschulschrift; Katalog; Werkverzeichnis